2015
DOI: 10.1128/aac.00352-15
|View full text |Cite
|
Sign up to set email alerts
|

Altered Competitive Fitness, Antimicrobial Susceptibility, and Cellular Morphology in a Triclosan-Induced Small-Colony Variant of Staphylococcus aureus

Abstract: Staphylococcus aureus can produce small-colony variants (SCVs) that express various phenotypes. While their significance is unclear, SCV propagation may be influenced by relative fitness, antimicrobial susceptibility, and the underlying mechanism. We have investigated triclosan-induced generation of SCVs in six S. aureus strains, including methicillin-resistant S. aureus (MRSA). Parent strains (P0) were repeatedly passaged on concentration gradients of triclosan using a solid-state exposure system to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 45 publications
5
40
0
2
Order By: Relevance
“…Minimum bactericidal concentrations were determined as described previously (14,33). Briefly, aliquots (10 l) from wells exhibiting no turbidity were transferred to sterile TSA prior to 4 days of incubation at 37°C to determine the MBC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimum bactericidal concentrations were determined as described previously (14,33). Briefly, aliquots (10 l) from wells exhibiting no turbidity were transferred to sterile TSA prior to 4 days of incubation at 37°C to determine the MBC.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously assessed the effect of formulation (29,30), growth in taxonomically diverse biofilm communities (31), and potential impairment of fitness in biocideadapted bacteria (32,33) in a series of studies intended to develop and apply methods for assessing the risk of biocide resistance based more closely on real-life conditions.…”
mentioning
confidence: 99%
“…Susceptibility of SCVs to three widely used antimicrobials (penicillin, gentamicin and triclosan) has been shown to reduce notably (Seaman et al, 2007). Small colony variants of Staphylococcus aureus, first described 100 years ago are more resistant to antibiotics (Proctor et al, 1998) than normal colonies; however, Forbes et al (2015) found that triclosan susceptibility in all SCVs (which could be generated from 4/6 strains) was distinctly declined, while antibiotic susceptibility was considerably augmented in most of the cases. Clinical studies suggest a link between electron transport-defective strains and persistent infections, a defined hemB mutant with SCV phenotype provided strong additional evidence for these connections (Von Eiff C et al, 2000A).…”
Section: Discussionmentioning
confidence: 97%
“…Staphylococcus aureus can produce small-colony variants (SCVs) that express different phenotypes. While their importance is uncertain, SCV propagation may be influenced by relative fitness, antimicrobial susceptibility, and the underlying mechanism (Forbes et al, 2015). Some workers were unable to demonstrate development of resistance following exposure of S.aureus to sub-minimum inhibitory concentrations of triclosan (Suller & Russell, 2000) but low-level resistance had been reported previously in Escherichia coli and S. aureus including MRSA (Cookson et al, 1991); the resistance in these organisms is due to either fabI mutation leading to over-expression of reductase or over-expression of efflux pumps (Bayston et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation